2022
DOI: 10.1101/2022.06.05.494587
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of Klebsiella pneumoniae mucoidy by the bacterial tyrosine kinase Wzc

Abstract: Klebsiella pneumoniae is a frequent nosocomial pathogen associated with urinary tract infections (UTI), pneumonia, and septicemia. Two lineages of K. pneumoniae have emerged that challenge the treatment of these infections. One lineage includes hypervirulent strains, causing invasive community-acquired infections, and the other encompasses carbapenem-resistant isolates. Non-mucoid, carbapenem-resistant isolates are most frequently isolated from UTI. Therefore, we hypothesized that environmental conditions may … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…S6A). This is also in line with recent research showing that some wzc mutations in trans lead to HMV 61 and it further underlines the complex regulatory pathway leading to the hypermucoviscous phenotype 43,44 . It will be important to test whether the mechanisms of adaptation and the advantage of the capsule are similar in more complex environments, for instance, in mixed bacterial communities.…”
Section: Discussionsupporting
confidence: 89%
“…S6A). This is also in line with recent research showing that some wzc mutations in trans lead to HMV 61 and it further underlines the complex regulatory pathway leading to the hypermucoviscous phenotype 43,44 . It will be important to test whether the mechanisms of adaptation and the advantage of the capsule are similar in more complex environments, for instance, in mixed bacterial communities.…”
Section: Discussionsupporting
confidence: 89%
“…A possible role of mutations localized within key conformationally labile regions could be to impart fitness in pathogenic species by altering the stabilities of the OS and CS, thereby affecting the relative lifetimes of Σ Μ and Σ Ο and allowing rapid adaption to environmental cues. It has been shown that Wzc mutations enable drug-resistant strains of Klebsiella pneumoniae to adapt to the urinary tract by regulating mucoidy ( 67 ). G569, which lies on α4 (rigid body motions of α4 distinguish the CS and OS; Fig.…”
Section: Dynamic Regions As Hot Spots For Adaptationmentioning
confidence: 99%
“…2 ). Furthermore, an insertion at the C-terminal end of α2 (at position 526) was also found to enhance mucoidy without reducing kinase activity ( 67 ). It is notable that this insertion coincides with the region modified to generate the G 4 -construct that stabilizes the CS in E. coli Wzc ( 22 ), as discussed previously ( Fig.…”
Section: Dynamic Regions As Hot Spots For Adaptationmentioning
confidence: 99%
“…Hypermucoviscosity is caused by changes in capsular polysaccharide chain length (Khadka et al., 2023; Ovchinnikova et al., 2023). Mucoviscosity was conventionally measured by the ‘string test’.…”
Section: Commentarymentioning
confidence: 99%
“…So far, more than 80 capsular types have been identified in the K. pneumoniae complex (Pan et al., 2015). Additionally, hypermucoviscosity is a unique virulence feature of K. pneumoniae , characterized by sticky bacterial colonies and associated with changes in capsule polymer chain length (Khadka et al., 2023; Ovchinnikova et al., 2023). The capsule protects K. pneumoniae from opsonophagocytosis and complement‐mediated killing, while hypermucoviscosity is often associated with increased dissemination in the host (Domenico et al., 1994; Mike et al., 2021).…”
Section: Introductionmentioning
confidence: 99%